Oral Roberts and the Rise of the Prosperity Gospel Jonathan Root: Grand Rapids: Eerdmans, 2023; xiv + 395 pp, $26.00, pb; ISBN 978-0-8028-7727-7 - Kjøde, Rolf (European journal of theology, 2025)
Jonathan Root gives an overview of the life and work of the late evangelist and prosperity gospel agent Oral Roberts. The presentation follows Roberts’ life chronologically and is thus a resource to understand his life and ministry from his simple and even poor childhood through growth, success and failures. Only in the epilogue does the author step forward with some discussion of Roberts’ role in the area of prosperity theologies and the relationship between the gospel and American culture.